The Effect of Competence, Motivation and Commitment on Nurse Performance - Jaksa, Suherman (Greenation Publisher & Yayasan Global Research National, 2024)
This study was conducted with the aim of obtaining various data collected analyzed and interpreted so as to obtain an overview of competence, motivation, commitment and performance and analyze the effect of competence, motivation and commitment on Nurse performance, both simultaneously and partially. The method used is descriptive survey method and explanatory survey. The type of investigation in this study is causality. The unit of analysis was the nurses of RSU Santosa Hospital Bandung Central with a sample of 50 nurses. The time horizon in this study is cross sectional and the analysis method used is frequency distribution and path analysis. The findings of this study are the motivation of nurses at RSU Santosa Hospital Bandung Central is appropriate, the competence of nurses is appropriate; in accordance with the needs, the commitment that has been established is quite good; the performance of nurses has high performance. Competence, motivation and commitment together affect the performance of nurses at Santosa Hospital Bandung Central. However, partially motivation is more dominant in influencing the performance of nurses than competence and commitment.